A Bicapped Trigonal-Prismatic Lead Complex: Catena-Poly[[[Aquabis(1,10-phenanthroline-κN,N′)lead(II)]-μ-Squarato-κO:κO,O] Dihydrate] - Uçar, I.; Bulut, A.; Kazak, C. (Int Union Crystallography, 2005)
The asymmetric unit of the title compound, {[Pb(C4O 4)-(C12H8N2)2(H 2O)]·2H2O}n, contains one squarate dianion, two phenanthroline (phen) ligands and one aqua ligand all coordinated to Pb, and two solvent water molecules. The eight-coordinate Pb metal ion displays a distorted bicapped trigonal-prismatic coordination environment, defined by three squarate O atoms, four N atoms from two chelating phen ligands and one O atom from the coordinated water molecule. The crystal structure contains chains of squarate-1,2,3-bridged PbII ions running in the [010] direction. These polymeric chains are linked to one another via offset face-to-face π-π interactions between the phen ligands, which lead to a two-dimensional network extending along the (001) plane. The crystal structure is also stabilized by O-H⋯O intermolecular hydrogen-bond interactions, forming a three-dimensional network. © 2005 International Union of Crystallography.
[[aquabis(1,10- Phenanthroline-Κ2n,n′)lead(ii)